Intravenous Perampanel as an Interchangeable Alternative to Oral Perampanel: A Randomized, Crossover, Phase I Pharmacokinetic and Safety Study. Issue 7 (20th May 2022) - Hussein, Ziad; Majid, Oneeb; Boyd, Peter; Aluri, Jagadeesh; Ngo, Leock Y; Reyderman, Larisa
Abstract: Intravenous (IV) drug administration enables treatment of epilepsy when oral administration is temporarily not feasible. Perampanel is a once‐daily antiseizure medication currently available as oral formulations. Study 050 (NCT03376997) was an open‐label, randomized, single‐dose, crossover study to evaluate the interchangeability of oral and IV perampanel in healthy subjects (N = 48). Bioequivalence of single 12‐mg doses of IV (30‐, 60‐, or 90‐minute infusion) and oral perampanel, ≥6 weeks apart, was assessed. Analyses indicated bioequivalence of area under the plasma concentration–time curve extrapolated to infinity for 30‐ and 60‐minute IV infusions and oral perampanel doses (geometric mean ratio [90% confidence interval], 0.93 [0.84–1.02] and 1.03 [0.97–1.09], respectively); however, IV maximum observed drug concentration (Cmax ) values were 1.35‐ to 1.61‐fold higher than Cmax . Simulated plasma concentration–time profiles using pooled pharmacokinetic data further supported oral and IV perampanel interchangeability in two scenarios: 12‐mg per day IV dosing during a temporary 7‐day switch from oral steady‐state maintenance therapy, and treatment initiation with 2‐mg perampanel. Thirty‐four (70.8%) subjects experienced treatment‐related adverse events. The IV perampanel safety profile was similar to that of oral perampanel without new safety concerns. Perampanel IV infusions may be a suitable temporary alternative to oral perampanel for treatment maintenance and/or initiation.